DIY History | Transcribe | Scholarship at Iowa | Eccentricity of the Sextant by Frederic Furbish, 1893 | Eccentricity of the Sextant by Frederic Furbish, 1893, Page 35

By Geometry BCD=CDE+BED BED=BCD-CDE But- BCD=2ACDonce CDE=2CDF, BED=2ACD-2CDF= 2(ACD-CDF). By Geometry ACD=CDF+AFD. AFD=ACD-CDF BED=2AFD= twice the angle between the reflecting surfaces C and D
The application of this principle to the [?] is shown very well in the following diagram and explanation. Suppose we [with] to observe the angular distances between the plain B and C, B being the [?] and C the familiar. Point the [?] at C and [?] the [?} so that its place [?] in the plane of the [?] As they are practically at the distance the says C D and

By Geometry BCD=CDE+BED BED=BCD-CDE But- BCD=2ACDonce CDE=2CDF, BED=2ACD-2CDF= 2(ACD-CDF). By Geometry ACD=CDF+AFD. AFD=ACD-CDF BED=2AFD= twice the angle between the reflecting surfaces C and D
The application of this principle to the [?] is shown very well in the following diagram and explanation. Suppose we [with] to observe the angular distances between the plain B and C, B being the [?] and C the familiar. Point the [?] at C and [?] the [?} so that its place [?] in the plane of the [?] As they are practically at the distance the says C D and